Respon Berbagai Sumber Bahan Stek terhadap Kemampuan Berakar Stek Alstonia scholaris (L) R. Br. sebagai Upaya Penyediaan Bibit untuk Lahan Terdegradasi - Kiki Ayunda Putri; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2017)
The research about the respon of the material cuttings retrieval on rooting ability of Alstonia scholaris (L.) R. Br. Cuttings in an effort provision of seeds for Degraded lands , conducted from October until December 2015 at Physiology Plant Laboratorium of Biology Department, Mathematics and Natural Science Faculty of Andalas University, Padang. The aim of this research to found the best material cuttings on A. scholaris. This research used Completely Randomized Design (CRD) method. The treatments were the basal (A), the middle (B), and the apical (C). The results showed that the apical was the best material cuttings, with a average number of roots (3.967), and the average of root dry weights (0.832)g. The conclusion of this research is the that material cuttings of apical is the bst one for Pulai cutting.